2022
DOI: 10.3389/fpsyg.2022.1007983
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness mediates the relationship between positive parenting and aggression, depression, and suicidal ideation: A longitudinal study in middle school students

Abstract: Previous research has indicated that parenting factors affect the risk of maladaptive psychological outcomes (e.g., aggression, depression, or suicidal ideation), and that positive parenting is a prospective risk factor for maladaptive psychological outcomes. However, the mechanisms underlying the relationships between positive parenting, mindfulness, and maladaptive psychological outcomes remain unknown, as do the processes that mediate the effect of positive parenting on maladaptive psychological outcomes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 134 publications
0
3
0
Order By: Relevance
“…result of a learning process. Feldman argued that at different stages the characteristics of child development are more prominent than other characteristics (Somantri, 2006).…”
Section: Positive Parenting Training For Increasing Self-acceptance O...mentioning
confidence: 99%
See 1 more Smart Citation
“…result of a learning process. Feldman argued that at different stages the characteristics of child development are more prominent than other characteristics (Somantri, 2006).…”
Section: Positive Parenting Training For Increasing Self-acceptance O...mentioning
confidence: 99%
“…Parents need to know that every child has strengths and weaknesses. Existing deficiencies will be covered with these advantages (Su et al, 2022). When a child with learning difficulties for example.…”
Section: Positive Parenting Parents With Children With Special Needsmentioning
confidence: 99%
“…According to the various systematic reviews and meta-analyses by these authors, Kong et al (2015) , Garland et al (2017) , McConville et al (2017) , Feller et al (2018) , Li (2021) , Søvold et al (2021) , Tan et al (2021) , Mubarak et al (2022) , Su et al (2022) and all these authors have suggested that therapies like mindfulness training may improve PWB. Similarly, it is mentioned that an enhanced level of mindfulness is shown to have a significant relationship with reducing depression and stress, leading to better self-control and a more positive outlook on life ( Lo et al, 2018 ; Epel et al, 2019 ) Mindfulness-based training has been studied extensively for its potential to improve mental health and happiness.…”
Section: Literature Reviewmentioning
confidence: 99%